Pengaruh Literasi Keuangan, Perilaku Keuangan, Herding Behavior, Risk Tolerance, dan Overconfidence terhadap Keputusan Investasi Pasar Modal (Studi Kasus pada Mahasiswa Universitas Muhammadiyah Surakarta) - Dewanti, Adinda Pramesdya Rasita; Triyono (Jurnal EMT KITA, 2024)
The purpose of this study was to analyze the effect of financial literacy, financial behavior, herding behavior, risk tolerance, and overconfidence on capital market investment decisions (case study on students of Universitas Muhammadiyah Surakarta). This type of research is quantitative. The population used in this study were Accounting students at Universitas Muhammadiyah Surakarta in the class of 2020. This study uses a sample withdrawal method, namely the NonProbability Sampling method using Purposive Sampling technique. The number of samples used in this study were 311 respondents. The data in this study are primary data. The data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, and hypothesis testing. The result of this study is that financial literacy has no significant effect on investment decision making. A person's financial behavior does not affect his investment decisions.  Herding behavior has a significant effect on investment decisions. Risk tolerance affects investment decision making. Overconfidence affects investment decision making.